Catha edulis and Cathinone Effect on Bone Parameters and Adipokines Gene Expression in Obese Male Mice - Mustafa Ahmed, Alshagga; Zahurin, Mohamed; Norazlina, Mohamed; Atefehalsadat, Seyedan; Yan, Pan; Sharoen Lim, Yu Ming; Mohammed Abdullah, Alshawsh (Springer Nature, 2023)
This study aims to determine the effects of Catha edulis (Vahl) Forssk. ex Endl., Celastraceae, and its bioactive alkaloid, cathinone, on liver histology, gene expression of inflammatory biomarkers in white adipose tissue, hypothalamus, and histomorphological bone parameters. Thirty male mice (C57BL/6J) were fed a high-fat diet for 8 weeks, divided into 5 groups, and treated daily for another 8 weeks high-fat diet + vehicle (control), HFD + 15 mg/kg orlistat, high-fat diet + 200 mg/kg plant extract, high-fat diet + 400 mg/kg plant extract, and high-fat diet + 3.2mg/kg cathinone. Treatments were carried out once daily by gastric gavage. Blood and tissue samples were collected for histological, biochemical, and gene expression analysis. The results showed the plant extract (400 mg/kg) and cathinone (3.2 mg/kg) displayed a marked reduction of liver fatty changes. All treated groups showed higher serum adiponectin levels compared to the control group (p <0.05). Plant extract–treated groups showed upregulation of adiponectin gene expression in white adipose tissue, however, at the concentration of 200 mg/kg upregulated interleukin-6 in the hypothalamus; in addition, this group showed less-eroded surfaces and higher bone mass compared to control. Cathinone-treated group exhibited increased osteoblast and osteoclast surfaces compared to the plant extract treatment. The study concluded that the plant extract and cathinone treatment are associated with minimal fat steatosis in the liver of obese mice probably by upregulation of anti-inflammatory adiponectin gene expression in adipose tissue. At the concentration of 200 mg/kg, the plant extract showed a protective effect on bone loss compared to orlistat, while cathinone promotes bone formation and resorption by a centrally mediated mechanism.